Prodrug design : perspectives, approaches and applications in medicinal chemistry - Redasani, Vivekkumar K.; Bari, Sanjay B. ([Amsterdam] : Academic Press is an imprint of Elsevier, 2015)
Prodrug Design: Perspectives, Approaches and Applications in Medicinal Chemistry provides a focused overview of this critical area of drug discovery, as that continuous process strives not only to discover new drug compounds but also to modify the existing ones. This valuable primer supports this mission of drug development and its goal of reducing undesired effects and improving therapeutic effectiveness of drug compounds. Providing a unique compilation of data, insightful case studies, and review of existing literature in the area, the book will promote innovation in medicinal and pharmaceu.
5.1.1 Masking Taste and Odor5.1.2 Minimizing Pain at Injection Site; 5.1.3 Alteration of Drug Solubility; 5.1.4 Enhancement of Chemical Stability; 5.1.5 Prodrugs to Overcome Absorption Problems; 5.1.5.1 Enhancement of Oral Absorption; 5.1.5.2 Enhancement of Ophthalmic Absorption; 5.1.5.3 Enhancement of Percutaneous Absorption; 5.1.6 Prevention of Presystemic Metabolism; 5.1.7 Longer Duration of Action; 5.1.8 To Diminish Local and Systemic Toxicity of Drugs/Reduction of GI Irritability; 5.1.9 Site-Specific Drug Delivery; 5.1.10 Prodrug for Slow and Prolonged Release (Sustained Drug Action).
Online resource; title from PDF title page (ScienceDirect, viewed July 16, 2015).
Includes bibliographical references.
Keywords: Pharmaceutical chemistry; Drugs -- Design; MEDICAL -- Pharmacology; Drugs -- Design; Pharmaceutical chemistry; Prodrugs; Drug Design; Electronic books; Electronic books